Unregistered births of adolescent mothers in Turkey: Invisible children - Faruk Keskin; Alanur Çavlin (Comparative Population Studies (CPoS), 2020)
This study examines birth registration for children of adolescent mothers based on family and citizenship concepts, and discusses the negotiation of registration practices between state and family in Turkey. The study is based on two data sources: official Turkish birth statistics from January 2009 to December 2015, and the Turkish Demographic and Health Survey from 2013 (TDHS-2013). We used TDHS-2013 to estimate birth registration completeness and timeliness in Turkey as of 2015. The results show 99 percent completion for birth registration of children under 5 years for the 2011-2015 period. For the same period, 98 percent of births to adolescent mothers were registered, but only 78 percent of all births to adolescent mothers were registered on time - within 30 days. Results indicate that the birth registration system is complete for Turkey in general, even for adolescent mothers, since their offspring are eventually registered, however the timeliness of registration is low for adolescent births. Late registration periods are shortening with time but the rights of unregistered children of adolescent mothers are slow to be recognized in cases where modern regulations of birth registration and traditional family practices collide.
urn:nbn:de:bib-cpos-2020-11en8
Keywords: 300; Turkey; Birth registration; Completeness; Adolescent birth; Citizenship; Family